FEATURES OF CONTROL WHEN EXTINGUISHING AIRCRAFT BY FIRE DEPARTMENTS - Vitaly V. Krymsky; Vladislav R. Golovenko (Модели, системы, сети в экономике, технике, природе и обществе, 2023)
Background. The assessment of modern methods of extinguishing aircraft fires in the Russian Federation was carried out. An assessment of the effectiveness of extinguishing aircraft braking systems during fires by various types of extinguishing agents has been carried out. Materials and methods. The method of expert assessments, the work of domestic specialists in the field of flight safety coordination, fire prevention and extinguishing, as well as scientific and theoretical materials of the Ministry of Transport of the Russian Federation, documentation of the Ministry of Emergency Situations of Russia, published results of scientific research and scientific papers in periodicals were used for the study. Results. As a result of the conducted analysis of fire extinguishing and emergency response during the emergency landing of aircraft, the need to provide fire protection units with modern samples of domestic fire fighting equipment of powder or combined extinguishing, which will help reduce the time of extinguishing fires, contributing to an increase in the time for the evacuation of passengers, was revealed. Conclusions. In the course of the analysis, the possibilities and prospects of the possibility of introducing the practice of powder or combined extinguishing to eliminate fires of aircraft braking systems by providing aerodrome fire departments with fire trucks of this type, which will increase the effectiveness of fire fighting and increase the percentage of rescued victims in such emergencies.